Cultural Adaptation and Validation of the Urdu Version of the Cognitive Emotion Regulation Questionnaire (CERQ) in Male Patients With Substance Use Disorders (SUDs) in Pakistan - Shahzad, Salman; Bano, Nasreen; Begum, Nasreen; Jones, Hendrée E. (Frontiers in Psychiatry, 2022)
Background:High numbers of people with substance use disorders (SUDs) have common co occurring mental health problems. Emotion regulation plays a vital role in mental health problems and it has been acknowledged by psychologists.However, this measure has not been used in Pakistan on patients with mental health and SUDs to see the emotion regulation strategies using Urdu translated version. Present study aims to translated and adapt the Cognitive Emotion Regulation Questionnaire (CERQ) into the Urdu language and to determine its psychometric properties on male patients with SUD within the Pakistani context. Method:Male participants (N = 237) ages between 16-50 years (M= 29.74years, SD = 8.083) were recruited from four substance use treatment centers and hospitals situatedin Karachi.Participants completed demographic information, The Cognitive Emotion Regulation Questionnaire (Garnefski, Kraaij&Spinhoven, 2002), the Depression, Anxiety, and StressScale (DASS; Lovibond & Lovibond, 1995)and Self-Esteem Scale (RSES; Rosenberg, 1965) in Urdu. Results:Reliability of the Urdu version of The CERQ inferred by cronbach’s alpha and test retestreliability. The cronbach alpha for the CERQ total(cronbach alpha = .80) is adequate. Similarly, cronbach alpha for subscales i.e.,Self blame, (cronbach alpha =.76) acceptance (cronbach alpha =.78), rumination (cronbach alpha =.72), positive refocusing (cronbach alpha =.79), focus on planning (cronbach alpha =.89), positive reappraisal (cronbach alpha =.81) putting into perspective (cronbach alpha =.84) catastrophizing (cronbach alpha =.73) other blame (cronbach alpha =.70), test retest reliability of The CERQ is (.86). Both DASS total (Cronbach alpha = .95) and RSES (Cronbach alpha = .91) had adequate internal consistency. Further,cronbach alpha for subscales (depression = .88, anxiety = .90, stress = .82) is also adequate. Higher level of cognitive emotion regulationstrategies are significantly negatively associated with depression (r =-.238, p < .001), anxiety (r =-230, p < .001) and stress(r =-270, p < .001) and DASS Total (r = -.258, p < .001) and positively associated with self esteem (r = .298, p < .001). Conclusion:The Urdu version of CERQis a reliable measure for investigating cognitive emotion regulation strategies related to mental healthand SUDs in Pakistan.